2009
DOI: 10.1016/j.biomaterials.2009.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous and organized differentiation within embryoid bodies induced by microsphere-mediated delivery of small molecules

Abstract: Cell specification and tissue formation during embryonic development are precisely controlled by the local concentration and temporal presentation of morphogenic factors. Similarly, pluripotent embryonic stem cells can be induced to differentiate in vitro into specific phenotypes in response to morphogen treatment. Embryonic stem cells (ESCs) are commonly differentiated as 3D spheroids referred to as embryoid bodies (EBs); however, differentiation of cells within EBs is typically heterogeneous and disordered. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(141 citation statements)
references
References 54 publications
2
139
0
Order By: Relevance
“…55 Published studies have reported that microspheremediated delivery of cytokines results in more homogenous delivery throughout dense tissue constructs and improved cell differentiation, compared to exogenous treatment. 56,57 While these data do not include direct measurements of TGF-b1 diffusion, contractile protein expression is an important outcome of TGF-b1 delivery. Within rings, exogenous TGF-b1 supplementation and microsphere-mediated delivery resulted in contractile protein expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…55 Published studies have reported that microspheremediated delivery of cytokines results in more homogenous delivery throughout dense tissue constructs and improved cell differentiation, compared to exogenous treatment. 56,57 While these data do not include direct measurements of TGF-b1 diffusion, contractile protein expression is an important outcome of TGF-b1 delivery. Within rings, exogenous TGF-b1 supplementation and microsphere-mediated delivery resulted in contractile protein expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5,[30][31][32][33] As the relative effects of different microenvironmental parameters on stem cell fate are increasingly discovered, 34 it becomes important to understand how modulation of endogenous ECM and GF expression can be achieved by engineering physical forces such as hydrodynamics to direct stem cell differentiation. As indicated by the results of this study, the augmented number of genes increased in rotary environments at day 14 compared with static (Fig.…”
Section: Fig 4 Different Classes Of Extracellular Matrix (Ecm) (A-hmentioning
confidence: 99%
“…Differentiating aggregates are thought to mimic the environment of the peri-implantation embryo where interactions between various cell types facilitate inductive events. As in the embryo, one of the earliest events during aggregate-based stem cell differentiation is the organization of the cells into an outer epithelial layer of extraembryonic endoderm (ExE) cells surrounding an inner core of epiblast-like pluripotent cells (Coucouvanis and Martin 1995;Keller 1995;Abe, Niwa et al 1996;Grabel, Becker et al 1998;Coucouvanis and Martin 1999;Ungrin, Joshi et al 2008;Carpenedo, Bratt-Leal et al 2009). During embryonic development, precardiac mesoderm is in close contact with endoderm tissue which has been shown to play an inductive role as evidenced by the generation of beating cardiac tissue in cocultures of non-cardiogenic embryonic tissue explants and endodermal tissue (Orts Llorca 1963;Jacobson and Duncan 1968;Sugi and Lough 1994;Nascone and Mercola 1995;Schultheiss, Xydas et al 1995).…”
Section: Introductionmentioning
confidence: 99%